¿Los pacientes odontológicos están dispuestos a pagar por medidas de bioseguridad ante COVID-19? - Revollo-Fernández, Daniel Alfredo; Herrera-Miranda, Andrea Isabel (Horizonte Sanitario, 2022)
Objective: Estimate whether dental patients are willing to pay (DAP) more for their appointments knowing that the clinic where they attend implemented biosecurity measures to prevent the spread of COVID-19. Similarly, if said payment varies depending on the type of dental treatment, as well as if the patient has some type of comorbidity. Materials and methods: Development and application of online surveys to a sample of 423 dental patients in Mexico with different treatments and presence of comorbidity if they were willing to pay for their care in the face of the COVID emergency for biosecurity measures using a statistical analysis of means . The survey was applied in the months of September to November 2020. Results: It was estimated that approximately 32% would cancel their dental appointments for fear of contracting COVID-19; however, almost 45% would be DAP an extra amount in the appointment, if the office or clinic implements strict biosecurity measures. These percentages, both for appointment cancellation and willingness to pay additional, are increased if the patient has any comorbidity. Conclusions: The patients in the sample are willing to pay an excess amount for their appointments knowing that the offices have implemented biosafety measures, and more so if they are patients with some comorbidity. Likewise, these clinics could receive some support from the Government for the well-being of the entire society.Keywords: COVID-19; Odontology; Comorbidity; Biosecurity